2021
DOI: 10.1021/acssuschemeng.1c03041
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Promoted Rapid Nucleation of Carbon Dioxide Hydrates

Abstract: Gas hydrates offer solutions in areas like CO 2 sequestration and desalination. However, their formation is severely limited by long induction (wait) times for nucleation, which range from hours to days. Many existing nucleation promotion techniques involve chemical additives, which invite environmental and process-related concerns. Here, we report a simple, passive, and environmentally friendly technique to significantly promote the nucleation of CO 2 hydrates: magnesium (in pure and alloy forms) triggers nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 100 publications
(135 reference statements)
1
13
0
Order By: Relevance
“…Silver iodide (AgI) is a strong promoter of ice nucleation; it has been observed that AgI particles nucleate ice at a much lower supercooling on direct contact with water drops (the presence of the air–water–AgI line) compared to the case of AgI particles immersed inside the water droplet. Shaw et al reported that ice nuclei trigger faster nucleation of ice when placed on the water–air interface rather than being completely immersed. The benefits of three-phase nucleation have also been observed by the present group during nucleation of gas hydrates, which are ice-like solids of gas and water and form at high pressures and temperatures close to 0 °C.…”
Section: Introductionsupporting
confidence: 59%
“…Silver iodide (AgI) is a strong promoter of ice nucleation; it has been observed that AgI particles nucleate ice at a much lower supercooling on direct contact with water drops (the presence of the air–water–AgI line) compared to the case of AgI particles immersed inside the water droplet. Shaw et al reported that ice nuclei trigger faster nucleation of ice when placed on the water–air interface rather than being completely immersed. The benefits of three-phase nucleation have also been observed by the present group during nucleation of gas hydrates, which are ice-like solids of gas and water and form at high pressures and temperatures close to 0 °C.…”
Section: Introductionsupporting
confidence: 59%
“…The role of stirring is 2-fold: it helps to constantly renew the aqueous water interface and to dissipate the heat released as a result of hydrate formation in the reactor. Mechanical stirring may also help to reduce nucleation time greatly, but it may require high energy input . The hydrate formation experiment is initiated after the start of stirring, and the process is carried out for the period of 12–24 h. A thin film was detected on the interface of liquid CO 2 and water in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…It is essential to accelerate the CO 2 hydrate formation kinetics to develop a more environmentally friendly, economical, and sustainable CO 2 sequestration technology. , Kinetic promoters have proven to improve hydrate formation kinetics for carbon dioxide capture and storage and gas storage applications. Among kinetic promoters for hydrate formation, amino acids (protein building blocks) are more preferable to surfactants from a process operation point of view (foam formation) and environmental perspective . Veluswamy et al investigated the effect of three different amino acids, such as tryptophan, histidine, and arginine, on the kinetics of methane hydrate formation in stirred and unstirred tank reactors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the slow kinetics of gas hydrate formation is one of the most serious obstacles to implementing this technology. Therefore, the hydrate community has focused on using special additives, namely, gas hydrate promoters (GHPs), that can accelerate the hydrate formation. , GHPs are divided into thermodynamic and kinetic types . Thermodynamic GHPs such as tetrahydrofuran, tetra- n -alkyl ammonium halides, and cyclopentane alter the equilibrium conditions of gas hydrate formation toward higher temperatures and lower pressures. This means that they provide milder conditions for the hydrate formation, but the gas capacity of the hydrate decreases .…”
Section: Introductionmentioning
confidence: 99%
“…33−35 Therefore, the hydrate community has focused on using special additives, namely, gas hydrate promoters (GHPs), that can accelerate the hydrate formation. 23,36 GHPs are divided into thermodynamic and kinetic types. 37 Thermodynamic GHPs such as tetrahydrofuran, tetra-n-alkyl ammonium halides, and cyclopentane alter the equilibrium conditions of gas hydrate formation toward higher temperatures and lower pressures.…”
Section: ■ Introductionmentioning
confidence: 99%